Asian International Student and Asian American Student: Mistaken Identity and Racial Microaggressions - Yeo, HyeJin Tina; Mendenhall, Ruby; Harwood, Stacy Anne; Huntt, Margaret Browne (Journal of International Students, 2019)
This study examines the experiences of Asian American students who are mistaken as Asian international students; it provides insight into domestic students’ perceptions of and potential racial microaggressive experiences of international students. Drawing from racial microaggressions survey data of Asian Americans, this study highlights the multiple layers of overt racism, microaggressions, and xenophobia directed against students who are perceived as Asian international students. The Asian American students’ narratives reveal that international students are often racialized by skin color, English proficiency, and nationality, which reflect U.S. racist framings of Asian Americans. Thus, we argue that racial experiences of Asian international students should be addressed as a part of U.S. racial ideology, notions of Whiteness, and racial microaggressions on campus.